Engineering Electrospun Nanofibers for the Treatment of Oral Diseases - Yuanfei Wang; Yingnan Liu; Xiaopei Zhang; Xiaopei Zhang; Na Liu; Na Liu; Xixi Yu; Meihua Gao; Wanchun Wang; Tong Wu; Tong Wu; Tong Wu (Frontiers in Chemistry, 2021)
With the increase of consumption of high-sugar foods, beverages, tobacco, and alcohol, the incidence rate of oral diseases has been increasing year by year. Statistics showed that the prevalence of oral diseases such as dental caries, dental pulpal disease, and periodontal disease has reached as high as 97% in 2015 in China. It is thus urgent to develop functional materials or products for the treatment of oral diseases. Electrospinning has been a widely used technology that is capable of utilizing polymer solution to generate micro/nano fibers under an appropriate high voltage condition. Owing to their excellent structures and biological performances, materials prepared by electrospinning technology have been used for a wide range of oral-related applications, such as tissue restoration, controlled drug release, anti-cancer, etc. In this regard, this article reviews the application and progress of electrospun nanofibers to various oral diseases in recent years. Firstly, engineering strategies of a variety of nanofiber structures together with their resultant functions will be introduced. Then, biological functions of electrospun nanofibers as well as their applications in the treatment of oral diseases are summarized and demonstrated. Finally, the development viewpoint of functional nanofibers is prospected, which is expected to lay the foundation and propose the direction for further clinical application.